Pemenuhan Amanah Pengelolaan Kas Sesuai Standar Akuntansi Keuangan pada Masjid Al-Huda - Hafiz Surya Chandra Izwandi; Choirul Anwar; Ayatulloh Michael Musyaffi (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This applied study aims to develop a web-based cash management prototype for Masjid Al-Huda. The study addresses manual cash records, the absence of written procedures, unstructured transaction archives, and limited access to financial information for congregants. The prototype was developed using a partial Rapid Application Development approach through requirements planning, system design, and development. Data were obtained through observation, interviews with mosque administrators, and review of available cash records. The result is a localhost-based prototype that supports cash receipt and disbursement recording, cash recapitulation, cash flow report generation, document management, and public-information pages. The cash procedures and flowcharts were used as the procedural basis for the system design. Limited testing with the mosque treasurer indicated that the main functions were aligned with initial user needs, with improvement suggestions for account codes and transaction-category filters.